A method for detecting multiple types of heavy metal ions based on Raman spectroscopy
By coating quaternized xylan on the paper and adding a variety of anions through ion exchange, a detection test strip can be prepared that can detect a variety of heavy metal ions, which solves the problems of narrow detection range and poor selectivity in the prior art, and achieves quantitative detection with high selectivity and high sensitivity, which has the advantages of low cost and environmental protection.
Patent Information
- Application Number
- CN202510037698.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-10
AI Technical Summary
The prior art is difficult to achieve high selectivity, high sensitivity, fast and low cost quantitative detection of a variety of heavy metal ions, especially when using surface-enhanced Raman scattering (SERS) technology, the detection range is narrow and the selectivity is poor.
By reducing gold and silver ions using quaternized xylan, gold and silver nanoparticles were prepared and applied to the surface of the paper, and a variety of anions were added through ion exchange technology to prepare a detection test paper that could detect a variety of heavy metal ions. This method uses anion to react specifically with heavy metal cations to generate precipitates and proportionally affect the Raman signal, thereby achieving quantitative detection.
It realizes high selectivity and high sensitivity quantitative detection of various types of heavy metal ions, which has the advantages of low detection limit, fast, low cost, and green environmental protection, and effectively utilizes plant polysaccharide resources and reduces detection costs.
Smart Images

Figure CN119438179B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of food and environment detection and biomass resource utilization, and specifically relates to a method for detecting various types of heavy metal ions based on Raman spectroscopy. Background Art
[0002] Surface enhanced Raman scattering (SERS) is one of the most promising technologies for rapid detection of trace pollutants. However, unlike organic harmful compounds, heavy metal ions do not have Raman activity, so the detection of harmful heavy metal ions using SERS technology can only be achieved through indirect signal changes. For example, DNA / oligonucleotide-coupled dyes are used to label metal nanoparticles to detect heavy metal ions, or Raman-active ligands are used to react specifically with heavy metal ions to induce metal particle aggregation to produce the SERS effect.
[0003] However, the above methods require complex labeling procedures and are usually only suitable for detecting a certain type of heavy metal ion, with a narrow scope of application and poor selectivity. Therefore, achieving highly selective, highly sensitive, rapid, and low-cost quantitative detection of multiple types of heavy metal ions remains a technical bottleneck for SERS technology to detect heavy metal ions. Summary of the invention
[0004] In order to solve the shortcomings and deficiencies of the prior art, the object of the present invention is to provide a method for detecting various types of heavy metal ions based on Raman spectroscopy.
[0005] The present invention uses quaternized xylan to reduce gold and silver ions and coats gold and silver nanoparticles on the surface of paper, and then immerses the coated paper in a solution containing multiple types of anions for ion exchange, thereby preparing a test paper capable of detecting multiple types of heavy metal ions; when the test paper is used for heavy metal ion detection, different anions react specifically with specific heavy metal cations to generate precipitation, which proportionally affects the Raman signal, thereby achieving highly selective and highly sensitive quantitative detection of different types of heavy metal cation pollutants. The method of the present invention has the advantages of low detection limit, high sensitivity, and the ability to quantitatively detect multiple types of heavy metal ion pollutants, and also has the advantages of simple test paper preparation method, low cost, and green environmental protection.
[0006] The purpose of the present invention is achieved through the following technical solutions:
[0007] A method for detecting multiple types of heavy metal ions based on Raman spectroscopy comprises the following steps:
[0008] (1) Preparation of test strips
[0009] The quaternary ammonium xylan is used to prepare gold nanoparticles through a reduction reaction to obtain a quaternary ammonium xylan / gold nanoparticle dispersion, which is then coated on the surface of paper; silver nanoparticles are then in-situ reduced on the surface of the paper to obtain a xylan coating test paper platform;
[0010] The xylan coating test paper platform is subjected to ion exchange with a solution containing anions, and Raman beacon molecules are added to the test paper after ion exchange to prepare the test paper; the anions are one or more of phosphate ions, sulfate ions, silicate ions, nitrate ions, carbonate ions, iodide ions, and bromide ions;
[0011] (2) Establishing a standard curve
[0012] Prepare a standard heavy metal cation solution, and drop the standard heavy metal cation solution on the surface of different test strips (each test strip is only dripped with a solution of a specific heavy metal cation and a specific concentration, so as to collect Raman spectra of heavy metal cations at different concentrations). The anions carried by the quaternary ammonium xylan in the test strip undergo a precipitation reaction with the heavy metal cations, and interfere with the Raman signal in proportion. Perform Raman spectroscopy on the test strips after the reaction, and establish a Raman signal standard curve of the test strips through Raman spectroscopy. The heavy metal cation in step (2) is Cd 2+ , Pb 2+ 、Co 2+ One or more of the following, among which Cd 2+ The concentration of the standard solution is 10 -3 mol / L~10 -9 mol / L; Pb 2+ The concentration of the standard solution is 200~0.1ppm; Co 2+ The concentration of the standard solution is 10 -3 mol / L~10 -7 mol / L;
[0013] (3) Perform Raman spectroscopy on the solution to be tested
[0014] The test solution containing heavy metal cations is dropped onto the surface of the test paper prepared in step (1), and the anions carried by the quaternized xylan in the test paper react with the heavy metal cations to cause precipitation, interfering with the Raman signal in proportion; the solution after the reaction is subjected to Raman spectroscopy detection, and the concentration of the heavy metal cations can be calculated by calculating the Raman signal standard curve of the corresponding heavy metal cations, thereby realizing the quantitative detection of the heavy metal cations in the test solution; the metal cation in step (3) is Cd 2+ , Pb 2+ 、Co 2+ One or more of the following.
[0015] Preferably, the quaternized xylan used in step (1) is obtained by modifying xylan with a xylan quaternizing agent; the xylan quaternizing agent is one of 3-chloro-2-hydroxypropyltrimethylammonium chloride, hexadecyltrimethylammonium chloride, 2,3-epoxypropyltrimethylammonium chloride, dodecyltrimethylammonium chloride, tetrabutylammonium chloride, etc.; and the molar ratio of xylan to the quaternizing agent is 1:1 to 1:1.5.
[0016] Preferably, the gold source used in preparing the gold nanoparticles in step (1) is tetrachloroauric acid trihydrate (HAuCl4·3H2O), and the mass ratio of tetrachloroauric acid trihydrate to quaternized xylan is 5-40 mg: 0.1-2 g; the reduction reaction time is 30-60 min, and the reduction reaction temperature is 70-90 °C. The coating amount of gold nanoparticles is 1.5-6.5 g / m 2 .
[0017] Preferably, the specific steps of in-situ reduction of silver nanoparticles on the paper surface in step (1) are: placing the paper coated with the gold nanoparticle dispersion into a Tollens reagent at 50-80°C for reaction for 30-60 min, depositing the silver nanoparticles obtained by in-situ reduction on the surface of the paper coated with the quaternary ammonium xylan gold nanoparticles, and then vacuum drying the treated test paper at 50°C for 12-24 h.
[0018] More preferably, the Tollens reagent is prepared by mixing 0.5-5 mL of 1-4 wt% sodium hydroxide solution and 0.6-1.5 mL of 0.01-0.1 mol / L silver nitrate standard solution, and then adding ammonia water until the precipitate just disappears.
[0019] Preferably, in step (1), a solution containing anions is used to perform ion exchange treatment on the xylan coating test paper platform, the concentration of anions in the solution containing anions is 0.01 mol / L~1 mol / L, the ion exchange time is 1~3 h, and vacuum drying is performed after the ion exchange reaction is completed.
[0020] More preferably, the vacuum drying temperature is 40-70° C. and the time is 30-60 min.
[0021] Preferably, the ion exchange method used in step (1) is at least one of impregnation and elution.
[0022] Preferably, in step (1), the Raman beacon molecule is added to the test paper after ion exchange, specifically, the Raman beacon molecule solution is dripped onto the surface of the test paper after ion exchange, and then dried at room temperature; the Raman beacon molecule is at least one of 4-thiobenzoic acid (4-MBA), crystal violet (CV), and rhodamine 6G (R6G).
[0023] More preferably, the solution system used to dissolve the Raman beacon molecules is at least one of water, methanol-chloroform, and anhydrous ethanol; the concentration of the Raman beacon molecule solution is 10-100 mmol / L, and the ratio of the amount of the Raman beacon molecule solution added to the paper area is 10 μL: 5 cm 2 .
[0024] Preferably, the Raman spectrum wavelength used in the Raman spectrum detection in steps (2) and (3) is at least one of 532 nm, 633 nm, and 785 nm, and the intensity of the Raman spectrum used is at least one of 5%, 3.2%, 1%, and 0.1%.
[0025] Preferably, the concentration of heavy metal cations in the test solution in step (3) is 0.01 mol / L~10 -15 mol / L.
[0026] In one preferred embodiment, the anion in step (1) is an iodide ion, and the heavy metal cation in step (3) is Cd 2+ .
[0027] In one preferred embodiment, the anion in step (1) is sulfate ion, and the heavy metal cation in step (3) is Pb 2+ .
[0028] In one preferred embodiment, the anions in step (1) are phosphate ions and iodide ions, and the heavy metal cations in step (3) are Co 2+ 、Cd 2+ One or more of the following.
[0029] In one preferred embodiment, the anions in step (1) are sulfate ions and phosphate ions, and the heavy metal cations in step (3) are Co 2+ , Pb 2+ One or more of the following.
[0030] The present invention also provides a test paper capable of detecting multiple types of heavy metal ions, which is prepared by the following steps:
[0031] (A) A gold source is added to a quaternary ammonium xylan dispersion to obtain a quaternary ammonium xylan / gold nanoparticle dispersion, which is then coated on the surface of paper; the paper is then immersed in a Tollens reagent and reacted at 50-80°C for 30-60 min to in-situ reduce the silver nanoparticles and deposit them on the coating surface, and then vacuum dried to obtain a xylan coating detection test paper platform;
[0032] (B) exchanging the xylan coating test paper platform with a solution containing anions for 1 to 3 hours, and vacuum drying after the reaction is completed; the anion solution is a solution containing one or more of phosphate ions, sulfate ions, silicate ions, nitrate ions, carbonate ions, iodide ions, and bromide ions;
[0033] (C) Dropping the Raman beacon molecule solution onto the surface of the test paper after ion exchange, and drying to obtain the test paper.
[0034] In a more preferred embodiment, in step (A):
[0035] The gold source is tetrachloroauric acid trihydrate (HAuCl4·3H2O), the mass ratio of tetrachloroauric acid trihydrate to quaternized xylan is 5-40 mg: 0.1-2 g, and the coating amount of gold nanoparticles is 1.5-6.5 g / m 2 ;
[0036] The vacuum drying is performed at 50° C. for 12 to 24 h.
[0037] In a more preferred embodiment, in step (B):
[0038] The concentration of the anion in the solution is 0.01 mol / L to 1 mol / L;
[0039] The vacuum drying temperature is 40-70°C and the time is 30-60 min;
[0040] The ion exchange method used is at least one of immersion and elution.
[0041] In a more preferred embodiment, in step (C):
[0042] The concentration of the Raman beacon molecule solution is 10-100 mmol / L;
[0043] The solution system used to dissolve the beacon molecule is at least one of water, methanol-chloroform, and anhydrous ethanol; the Raman beacon molecule is at least one of 4-thiobenzoic acid (4-MBA), crystal violet (CV), and rhodamine 6G (R6G);
[0044] The drying is natural drying at room temperature.
[0045] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0046] (1) The method for detecting multiple types of heavy metal ions based on Raman spectroscopy described in the present invention can realize the detection of multiple types of heavy metal ions.
[0047] (2) Compared with other heavy metal ion detection methods, the method for detecting multiple types of heavy metal ions based on Raman spectroscopy described in the present invention has high selectivity, is applicable to a wide variety of heavy metal ions, and has high detection sensitivity, and can achieve rapid quantitative detection.
[0048] (3) The test paper provided by the present invention has the advantages of simpler preparation method, mild preparation conditions, and green and biodegradable.
[0049] (4) The preparation method of the test strip provided by the present invention effectively utilizes the plant polysaccharide resources in the pulp and paper making and agricultural and forestry biomass processing industries, and utilizes the plant polysaccharide resources to replace the expensive oligosaccharides, ribose, etc. in the SERS technology, thereby reducing the cost and realizing the high-value utilization of the plant polysaccharide resources. It provides a new approach for plant polysaccharide resources and SERS technology and has good economic value. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 For Blank, QX@Au R6G, I1 R6G Blank, I1 R6G 10 in Example 1 -3 C 2+ Raman spectrum.
[0051] Figure 2 10 is detected after treatment under pH=5.5~10.5 conditions in Example 1 -3 mol / L Raman spectrum of cadmium ion.
[0052] Figure 3 is the Cr in step (3) of Example 1 3+ 、Cd 2+ , Pb 2+ , Fe 3+ Mg 2+ 、Co 2+ ,Ge 2+ 、Zn 2+ Raman spectrum of metal ion detection 611cm -1 The strength of the place.
[0053] Figure 4 Example 1 Ion exchange test paper capable of detecting various types of heavy metal ions I1 Raman spectrum 611cm -1 The peak intensity at different Cd 2+ Concentration fitting curve plot.
[0054] Figure 5 The ion exchange test paper of Example 1 can detect various types of heavy metal ions. 744 cm in the Raman spectrum of I1 -1 The peak intensity at different Cd 2+ Concentration fitting curve plot.
[0055] Figure 6 The ion exchange test paper of Example 1 can detect various types of heavy metal ions. 1183cm in the Raman spectrum -1 The peak intensity at different Cd 2+ Concentration fitting curve plot.
[0056] Figure 7 The ion exchange test paper S1 of Example 2 can detect various types of heavy metal ions. 611cm in the Raman spectrum -1 The peak intensity at different Pb 2+ Concentration fitting curve plot.
[0057] Figure 8 The ion exchange test paper S1 of Example 2 can detect various types of heavy metal ions. 744cm in the Raman spectrum -1 The peak intensity at different Pb 2+ Concentration fitting curve plot.
[0058] Fig. 9 The ion exchange test paper S1 of Example 2 can detect various types of heavy metal ions. 1183cm in the Raman spectrum -1 The peak intensity at different Pb 2+ Concentration fitting curve plot.
[0059] Fig.10 The 611cm in the Raman spectrum of the PI1 test paper for ion exchange that can detect various types of heavy metal ions in Example 3 -1 The peak intensity at different Co 2+ Concentration fitting curve plot.
[0060] Fig.11 The ion exchange test paper PI1 of Example 3 can detect various types of heavy metal ions. 744cm in the Raman spectrum -1 The peak intensity at different Co 2+ Concentration fitting curve plot.
[0061] Fig.12 The ion exchange test paper PI1 of Example 3 can detect various types of heavy metal ions. 1183cm in the Raman spectrum -1 The peak intensity at different Co 2+ Concentration fitting curve plot.
[0062] Fig.13 The ion exchange test paper PS1 of Example 4 can detect various types of heavy metal ions. 611cm in the Raman spectrum -1 The peak intensity at different Pb 2+ Concentration fitting curve plot.
[0063] Fig.14The ion exchange test paper PS1 of Example 4 can detect various types of heavy metal ions at 744 cm in the Raman spectrum. -1 The peak intensity at different Pb 2+ Concentration fitting curve plot. DETAILED DESCRIPTION
[0064] The present invention is further described in detail below in conjunction with the examples and drawings, but the embodiments of the present invention are not limited thereto. The raw materials involved in the present invention can be purchased directly from the market. For process parameters not particularly noted, conventional techniques can be used.
[0065] Example 1
[0066] (1) 3-Chloro-2-hydroxypropyltrimethylammonium chloride was used to quaternize xylan (molar ratio 1:1) to obtain quaternized xylan. 3 g of 10 wt% quaternized xylan aqueous solution was used to reduce 5 mg of tetrachloroauric acid trihydrate to obtain a quaternized xylan / gold nanoparticle dispersion; the dispersion was coated on the surface of paper and then treated with Tollens reagent (mixing 2 mL of 0.2 wt% sodium hydroxide and 0.6 mL of 0.1 mol / L silver nitrate solution and adding ammonia water until the precipitate disappeared to prepare the Tollens reagent) at 60 °C for 45 minutes. After the reaction, the dispersion was placed in a vacuum drying oven at 50 °C for 12 h to reduce the silver nanoparticles in situ and deposit them on the surface of the quaternized xylan / gold nanoparticle coating to obtain a xylan-coated paper-based chip with a gold nanoparticle coating amount of 3.67 g / m 2 .
[0067] (2) The xylan-coated paper chip prepared in step (1) was impregnated with a 0.1 mol / L iodine ion solution for 3 h. After the reaction, it was placed in a vacuum drying oven at 60 °C for 30 min. After ion exchange, 100 μL of 10 mmol / L ethanol solution of rhodamine 6G (R6G) was added dropwise to the iodine-loaded xylan paper chip and dried at room temperature for 30 min to obtain an iodine ion exchange test paper I1 that can detect multiple types of heavy metal ions.
[0068] (3) Prepare the concentration of 10 -3 mol / L~10 -10 mol / LCr 3+ 、Cd 2+ , Pb 2+ , Fe 3+ Mg 2+ 、Co 2+ ,Ge 2+ 、Zn 2+ Metal ion standard solution (the concentration of cadmium ion standard solution is 10-3 mol / L~ 10 -9 mol / L, concentration gradient is 10 - 9 mol / L,10 -8 mol / L,10 -7 mol / L,10 -6 mol / L,10 -5 mol / L,10 -4 mol / L,10 -3 mol / L), and 10μL was added to different test strips I1 respectively, and the Raman spectra were collected using a 785nm light source with a laser intensity of 3.2%. The results showed that compared with the blank sample, the Raman spectrum of rhodamine 6G at 611cm -1 、744cm -1 、1183cm -1 Cadmium ions and iodine ions loaded on the paper-based chip produce precipitation interference Raman signals, and other metal ions do not cause significant interference to the Raman spectrum. The cadmium ion standard curve was calculated through Raman spectroscopy.
[0069] Figure 1 For Blank, QX@Au R6G, I1 R6G Blank, I1 R6G 10 in Example 1 -3 mol / L Cd 2+ Raman spectra. Blank is the Raman spectrum of untreated paper R6G, QX@Au R6G is the Raman spectrum of R6G paper with only gold nanoparticles, I1 R6G Blank is the Raman spectrum of R6G paper with I1 test paper, I1 R6G 10 -3 mol / L Cd 2+ Add Cd to the I1 test paper 2+ Raman spectrum of Cd ion standard solution. 2+ After the ion standard solution is added to the test paper, it forms a precipitate with the iodide ions on the paper surface to interfere with the Raman signal and quench the Raman signal intensity.
[0070] Figure 3 is the Cr in step (3) of Example 1 3+ 、Cd 2+ , Pb 2+ , Fe 3+ Mg 2+ 、Co 2+ ,Ge 2+ 、Zn 2+ Raman spectrum of metal ion detection 611cm -1 The intensity at the point. It can be seen in the figure that only Cd 2+Ions have a quenching effect on the Raman signal intensity of the test paper.
[0071] Figure 4~Figure 6 The ion exchange test paper of Example 1 can detect various types of heavy metal ions. The Raman spectrum of 611, 744, 1183 cm -1 The peak intensity at different Cd 2+ Concentration fitting curve. 10 -3 ~10 - 9 mol / L cadmium ion standard solution, and fitted the fitting curve of peak intensity changing with cadmium ion concentration. It can be observed that as the concentration of cadmium ion solution increases, the peaks at 611, 744, and 1183 cm -1 The peak intensity at the position decreases proportionally, and the fitting results are Y=-5096.71842X+15060.05988 (R 2 =0.98003), Y=-2922.27667X+7543.97054 (R 2 =0.97222), Y=-3154.71478+8646.34331 (R 2 =0.98138). Based on this fitting result, the concentration of cadmium ion solution is quantitatively analyzed. As can be seen from the figure, Cd 2+ The concentration is 10 -3 mol / L~10 -9 In the range of mol / L, Cd 2+ The concentration and Raman spectrum test results show a good linear relationship. It can be judged that the detection limit of the test paper I1 for the concentration of cadmium ion solution is 10 -9 mol / L.
[0072] (4) Set the configured 10 -6 10 μL of cadmium ion solution of mol / L was dropped onto the test paper I1, and the Raman spectrum was collected using a 785 nm light source and a laser intensity of 3.2%. The Raman spectrum of R6G was observed at 611, 744, and 1183 cm -1 The Raman intensity decreased everywhere, and the cadmium ion concentration was calculated by the standard curve to be 1.86×10 -6 mol / L.
[0073] In addition, the test paper I1 can detect cadmium ion solution normally under the condition of pH=5.5~10.5. After the test paper is treated with pH=5.5~10.5, 10 -3 For cadmium ion solutions with a concentration of mol / L, the intensity reduction of the Raman spectrum is within the error range.
[0074] Example 2
[0075] (1) 2, 3-Epoxypropyltrimethylol chloride was used to quaternize xylan (molar ratio 1:1) to obtain quaternized xylan. 5 g of 40 wt% quaternized xylan aqueous solution was used to reduce 25 mg of tetrachloroauric acid trihydrate to obtain a quaternized xylan / gold nanoparticle dispersion; the dispersion was coated on the surface of paper and then Tollens reagent (5 mL of 0.3 wt% sodium hydroxide and 1.5 mL of 0.05 mol / L silver nitrate solution were mixed and then ammonia water was added until the precipitate disappeared to prepare the Tollens reagent) at 80 °C for 40 minutes. After the reaction, the dispersion was placed in a vacuum drying oven at 50 °C for 12 h to reduce the silver nanoparticles in situ and deposit them on the surface of the quaternized xylan / gold nanoparticle coating to obtain a xylan-coated paper-based chip. The gold nanoparticle coating amount of the paper-based chip was 4.85 g / m 2 .
[0076] (2) The xylan-coated paper chip prepared in step (1) was impregnated with a sulfate ion solution having a concentration of 0.3 mol / L for 1 h. After the reaction, the chip was placed in a vacuum drying oven at 60 °C for 30 min. After ion exchange, 100 μL of an ethanol solution of rhodamine 6G (R6G) having a concentration of 10 mmol / L was added dropwise to the sulfate ion-loaded xylan paper chip and dried at room temperature for 30 min to obtain a sulfate ion exchange test paper S1 capable of detecting a variety of heavy metal ions.
[0077] (3) The concentration is 10 -3 mol / L~10 -10 mol / LCr 3+ 、Cd 2+ , Pb 2+ , Fe 3+ Mg 2+ 、Co 2+ ,Ge 2+ 、Zn 2+ 10 μL of the standard solution of metal ions was dripped onto different test strips S1 (the concentration of the standard solution of lead ions was 200-2ppm, and the concentration gradient was 2ppm, 10ppm, 20ppm, 50ppm, 100ppm, 200ppm), and the Raman spectrum was collected using a 633 nm light source with a Raman intensity of 3.2%. The results showed that compared with the blank sample, the Raman spectrum of rhodamine 6G at 611, 744, and 1183 cm -1 A significant decrease or enhancement was observed at the Raman spectroscopy site; the 200-2 ppm lead ion solution reacted with the sulfate ions loaded on the paper-based chip to generate precipitation that interfered with the Raman signal, while other metal ions did not significantly interfere with the Raman signal. The lead ion standard curve was calculated using Raman spectroscopy.
[0078] Figure 7~Figure 9 The ion exchange test paper S1 of Example 2 can detect various types of heavy metal ions. The Raman spectrum of 611, 744, 1183 cm -1 The peak intensity at different Pb 2+ Concentration fitting curve. 2~200ppm lead ion standard solution was added to S1 test paper, and the fitting curve of peak intensity changing with lead ion concentration was fitted. It can be observed that as the concentration of lead ion solution increases, the peaks at 611, 744, 1183cm -1 The peak intensity at the point decreases proportionally, and the fitting results are Y=88998.07234X^(-0.37472), Y=57236.63083X^(3914.23068), and Y=49530.24668X^(-0.36181). The concentration of the lead ion solution is quantitatively analyzed based on the fitting results. The fitting curve proves that the lead ion concentration is in the range of 200~2 ppm, and the lead ion concentration has a good linear relationship with the Raman spectrum detection results. It can be judged that the detection limit of the lead ion solution by the test paper S1 is 2 ppm.
[0079] (4) Drop 10 μL of the prepared 50 ppm lead ion solution onto the test paper S1, and collect the Raman spectrum using a 633 nm light source and a laser intensity of 3.2%. It was observed that the Raman spectrum of R6G was at 611, 744, and 1183 cm -1 A decrease in Raman intensity was observed everywhere, and the lead ion concentration was calculated to be 46 ppm using the standard curve.
[0080] In addition, after testing, the test paper S1 can normally detect lead ion solution under the condition of pH=5.5~10.5. After the test paper was treated under the condition of pH=5.5~10.5, a 100 ppm concentration of lead ion solution was added, and the degree of weakening of the Raman spectrum intensity was within the error range.
[0081] Example 3
[0082] (1) Hexadecyltrimethylammonium chloride was used to quaternize xylan (molar ratio 1:1.5) to obtain quaternized xylan. 5 g of 20 wt% quaternized xylan aqueous solution was used to reduce 10 mg of tetrachloroauric acid trihydrate to obtain a quaternized xylan / gold nanoparticle dispersion; the dispersion was coated on the surface of paper and then Tollens reagent (3.5 mL of 0.2 wt% sodium hydroxide and 1.2 mL of 0.01 mol / L silver nitrate solution were mixed and then ammonia water was added dropwise until the precipitate disappeared to prepare the Tollens reagent) at 70°C for 40 minutes. After the reaction, the dispersion was placed in a vacuum drying oven at 50°C for 12 h to reduce the silver nanoparticles in situ and deposit them on the surface of the quaternized xylan / gold nanoparticle coating to obtain a xylan-coated paper-based chip with a gold nanoparticle coating amount of 2.36 g / m 2 .
[0083] (2) The xylan-coated paper chip prepared in step (1) was eluted with a phosphate ion solution with a concentration of 0.5 mol / L for 1.5 h. After the reaction, it was placed in a vacuum drying oven at 60°C for 30 min. The xylan paper chip was then eluted with an iodine ion solution for 1.5 h. After the reaction, it was placed in a vacuum drying oven at 60°C for 30 min. After the ion exchange, 100 μL of an ethanol solution of rhodamine 6G (R6G) with a concentration of 10 mmol / L was added dropwise to the xylan paper chip loaded with phosphate and iodide ions and dried at room temperature for 30 min to obtain a phosphate and iodide ion exchange test paper PI1 that can detect multiple types of heavy metal ions.
[0084] (3) The concentration is 10 -3 mol / L~10 -10 mol / LCr 3+ 、Cd 2+ , Pb 2+ , Fe 3+ Mg 2+ 、Co 2+ ,Ge 2+ 、Zn 2+ 10 μL of the metal ion standard solutions were added to different test strips PI1 (the concentration of the cadmium ion standard solution was 10 - 3 mol / L~ 10 -9 mol / L, concentration gradient is 10 -9 mol / L,10 -8 mol / L,10 -7 mol / L,10 -6 mol / L,10 -5 mol / L,10 -4 mol / L,10 -3 mol / L; the concentration of the cobalt ion standard solution is 10 -3 mol / L~ 10 -7 mol / L, concentration gradient is 10 -7 mol / L,10 -6 mol / L,10 -5 mol / L,10 -4 mol / L,10 -3 mol / L), using a 633nm light source to collect Raman spectra, the laser intensity was 5%. The results showed that compared with the blank sample, the Raman spectrum of rhodamine 6G at 611cm -1 ,744 -1 ,1183 -1 Significant decrease or increase was observed in 10 -3 mol / L ~10 -9 The cadmium ion solution with a concentration of 10 mol / L reacts with the iodine ions on the paper-based chip to generate precipitation that interferes with the Raman signal. -3 mol / L ~10 -7 The cobalt ion solution with a concentration of mol / L and the phosphate ions loaded on the paper-based chip produced precipitation interference with the Raman signal, while other ions did not significantly interfere with the Raman signal. The standard curves of cadmium ions and cobalt ions were calculated by Raman spectroscopy.
[0085] The detection paper PI1 and Raman spectrum of 611, 744, 1183 cm -1 The peak intensity at and the fitting curve of different cadmium ion concentrations can be found in Figure 4~Figure 6 From the fitting curve Figure 4~Figure 6 It can be judged that the detection limit of the detection platform for cadmium ion solution is 10 -9 mol / L, Figure 10~Figure 12 The ion exchange test paper PI1 of Example 3 can detect various types of heavy metal ions. The Raman spectrum of 611, 744, 1183 cm -1 The peak intensity at different Co 2+ Concentration fitting curve. 10 -3 ~10 -7 mol / L cobalt ion standard solution, and fitted the fitting curve of peak intensity changing with cobalt ion concentration. It can be observed that as the concentration of cobalt ion solution increases, the peaks at 611, 744, and 1183 cm -1 The peak intensity at the position decreases proportionally, and the fitting results are Y=1341.21732X^(-0.1515) (R 2 =0.98658), Y=1613.67304X^(-0.07485) (R 2=0.99961), Y=1739.00076X^(-0.12686) (R 2 =0.98159). The fitting results are used to quantitatively analyze the concentration of cobalt ion solution. 2+ The concentration is 10 -3 mol / L~10 -7 In the range of mol / L, Co 2+ The concentration and Raman spectrum test results show a good linear relationship. It can be judged that the detection limit of the cobalt ion solution concentration of the test paper PI1 is 10 - 7 mol / L.
[0086] (4) Set the configured 10 -4 10 μL of mol / L cobalt ion solution was dropped onto the test paper PI1, and the Raman spectrum was collected using a 633 nm light source and a laser intensity of 5%. The Raman spectrum of R6G was observed at 611, 744, and 1183 cm -1 The Raman intensity decreased everywhere, and the cobalt ion concentration was calculated to be 2.76×10 -4 mol / L.
[0087] The configured 10 -5 10 μL of cadmium ion solution of mol / L was dropped onto the test paper PI1, and the Raman spectrum was collected using a 633 nm light source and a laser intensity of 5%. The Raman spectrum of R6G was observed at 611, 744, and 1183 cm -1 The Raman intensity decreased everywhere, and the cadmium ion concentration was calculated to be 1.83×10 -5 mol / L. It can be seen that the test paper PI1 can realize the quantitative detection of at least two heavy metal ions, cadmium and cobalt.
[0088] In addition, the test paper PI1 can detect cadmium and cobalt ion solutions normally under the condition of pH=5.5~10.5. -3 For cadmium ion solution and cobalt ion solution with mol / L concentration, the intensity reduction of Raman spectrum is within the error range.
[0089] Example 4
[0090] (1) 2, 3-Epoxypropyltrimethylol chloride was used to quaternize xylan (molar ratio 1:1) to obtain quaternized xylan. 5 g of 40 wt% quaternized xylan aqueous solution was used to reduce 25 mg of tetrachloroauric acid trihydrate to obtain a quaternized xylan / gold nanoparticle dispersion; the dispersion was coated on the surface of paper and then Tollens reagent (5 mL of 0.3 wt% sodium hydroxide and 1.5 mL of 0.05 mol / L silver nitrate solution were mixed and then ammonia water was added dropwise until the precipitate disappeared to prepare the Tollens reagent) at 80 °C for 40 minutes. After the reaction, the dispersion was placed in a vacuum drying oven at 50 °C for 12 h to reduce the silver nanoparticles in situ and deposit them on the surface of the quaternized xylan / gold nanoparticle coating to obtain a xylan-coated paper-based chip. The gold nanoparticle coating amount of the paper-based chip was 5.02 g / m 2 .
[0091] (2) The xylan-coated paper chip prepared in step (1) was impregnated with a 0.3 mol / L phosphate ion solution for 1 h. After the reaction, it was placed in a vacuum drying oven at 60°C for 30 min. The xylan paper chip prepared was impregnated with a 0.3 mol / L sulfate ion solution for 1 h. After the reaction, it was placed in a vacuum drying oven at 60°C for 30 min. After ion exchange, 100 μL of 10 mmol / L ethanol solution of rhodamine 6G (R6G) was added dropwise to the xylan paper chip loaded with phosphate and sulfate ions and dried at room temperature for 30 min to obtain sulfate ion exchange test paper PS1 that can detect multiple types of heavy metal ions.
[0092] (3) The concentration is 10 -3 mol / L~10 -10 mol / LCr 3+ 、Cd 2+ , Pb 2+ , Fe 3+ Mg 2+ 、Co 2+ ,Ge 2+ 、Zn 2+ 10 μL of the metal ion standard solutions were added to different test strips PS1 (the concentration of the lead ion standard solution was 0.1-100 ppm, with a concentration gradient of 0.1 ppm, 10 ppm, 25 ppm, 50 ppm, 75 ppm, and 100 ppm; the concentration of the cobalt ion standard solution was 10 -3 mol / L~ 10 -7 mol / L, concentration gradient is 10 -7 mol / L,10 -6 mol / L,10-5 mol / L,10 -4 mol / L,10 - 3 mol / L), using a 633 nm light source to collect Raman spectra, with a Raman intensity of 3.2%. The results showed that compared with the blank sample, the Raman spectra of rhodamine 6G at 611, 744, and 1183 cm -1 A significant decrease or increase was observed in the lead ion solution with a concentration of 0.1-100 ppm, -3 ~10 -7 The cobalt ions with different mol / L concentrations interfered with the Raman signal to varying degrees, while other ions did not significantly interfere with the Raman signal. The standard curves of lead and cobalt ions were calculated by Raman spectroscopy.
[0093] Test paper PS1 and Raman spectrum 611, 744, 1138cm -1 The peak intensity at and the fitting curve of different cobalt ion concentrations can be found in Figure 10~Figure 12 From the fitting curve Figure 10~Figure 12 It can be judged that the detection limit of the cobalt ion solution concentration of the test paper PS1 is 10 -7 mol / L; from the fitting curve Figure 13~Figure 14 It can be determined that the detection limit of lead ion solution concentration is 0.1ppm. Figure 13~Figure 14 The ion exchange test paper PS1 of Example 4 can detect various types of heavy metal ions, and the Raman spectrum of 611 and 744 cm -1 The peak intensity at different Pb 2+ Concentration fitting curve. 0.1~100ppm lead ion standard solution was added to the PS1 test paper, and the fitting curve of peak intensity changing with lead ion concentration was fitted. It can be observed that as the concentration of lead ion solution increases, the peak intensity at 611 and 744cm -1 The peak intensity at the point decreases proportionally, and the fitting results are Y=22709.9611X^(-0.39522) (R 2 =0.92798), Y=11971.63952X^(-0.333) (R 2 =0.95598). Based on this fitting result, the concentration of cadmium ion solution is quantitatively analyzed. It can be seen from the figure that Pb 2+ The concentration of Pb is in the range of 0.1~100 ppm. 2+ There is a good linear relationship between the concentration and the Raman spectrum detection result. It can be judged that the detection limit of the lead ion solution concentration of the test paper PS1 is 0.1ppm.
[0094] (4) Drop 10 μL of the prepared 25 ppm lead ion solution onto the test paper PS1, and collect the Raman spectrum using a 633 nm light source and a laser intensity of 5%. The Raman spectrum of R6G was observed at 611, 744, and 1183 cm -1 A decrease in Raman intensity was observed everywhere, and the lead ion concentration was calculated to be 27 ppm using the standard curve.
[0095] The configured 10 -5 10 μL of mol / L cobalt ion solution was dropped onto the test paper PS1, and the Raman spectrum was collected using a 633 nm light source and a laser intensity of 5%. The Raman spectrum of R6G was observed at 611, 744, and 1183 cm -1 The Raman intensity decreased everywhere, and the cobalt ion concentration was calculated to be 0.96×10 -5 mol / L.
[0096] It can be seen that the test paper PS1 can achieve quantitative detection of at least two heavy metal ions, lead and cobalt. Among them, the test paper PS1 can normally detect lead and cobalt ion solutions under the condition of pH=5.5~10.5. After the test paper is treated with pH=5.5~10.5, 10 -3 For cobalt ion solution with a concentration of mol / L and lead ion solution with a concentration of 5 ppm, the intensity reduction of Raman spectrum is within the error range.
[0097] Comparative Example 1
[0098] (1) 3-Chloro-2-hydroxypropyltrimethylammonium chloride was used to quaternize xylan (molar ratio 1:1) to obtain quaternized xylan. 3 g of 10 wt% quaternized xylan aqueous solution was used to reduce 5 mg of tetrachloroauric acid trihydrate to obtain a quaternized xylan / gold nanoparticle dispersion; the dispersion was coated on the surface of paper and then treated with Tollens reagent (mixing 2 mL of 0.2 wt% sodium hydroxide and 0.6 mL of 0.1 mol / L silver nitrate solution and adding ammonia water until the precipitate disappeared to prepare the Tollens reagent) at 60 °C for 45 minutes. After the reaction, the dispersion was placed in a vacuum drying oven at 50 °C for 12 h to reduce the silver nanoparticles in situ and deposit them on the surface of the quaternized xylan / gold nanoparticle coating to obtain a xylan-coated paper-based chip with a gold nanoparticle coating amount of 3.58 g / m 2 .
[0099] (2) Add 100 μL of 10 mmol / L ethanol solution of rhodamine 6G (R6G) to the xylan paper-based chip and dry it at room temperature for 30 min to obtain test paper I0.
[0100] The concentration of 10 -3 mol / L~10 -10 mol / LCr 3+ 、Cd 2+ , Pb 2+ , Fe 3+ Mg 2+ 、Co 2+ ,Ge 2+ 、Zn 2+ 10 μL of the standard solution of metal ions was added to different test strips I0 respectively, and the Raman spectrum was collected using a 785 nm light source with a Raman intensity of 5%. The Raman spectrum of rhodamine 6G was observed at 611, 744, and 1183 cm-1 in comparison with the blank sample. -1 No obvious decrease or increase was observed. This indicates that ion exchange is a good method for preparing the heavy metal ion Cd 2+ , Pb 2+ 、Co 2+ Necessary steps for the test strips.
[0101] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for detecting multiple types of heavy metal ions based on Raman spectroscopy, characterized in that: The following steps are involved: (1) Preparation of test strips The quaternary ammonium xylan is used to prepare gold nanoparticles through a reduction reaction to obtain a quaternary ammonium xylan / gold nanoparticle dispersion, which is then coated on the surface of paper; silver nanoparticles are then in-situ reduced on the surface of the paper to obtain a xylan coating test paper platform; The xylan-coated test paper platform is subjected to ion exchange with a solution containing anions, and Raman beacon molecules are added to the test paper after ion exchange to prepare a test paper; (2) Establishing a standard curve Prepare standard heavy metal cation solutions, drop the standard heavy metal cation solutions on the surfaces of different test strips, perform Raman spectroscopy on the test strips after the reaction, and establish a Raman signal standard curve of the test strips through Raman spectroscopy; The heavy metal cation in step (2) is Cd 2+ , Pb 2+ 、Co 2+ One or more of the following, among which Cd 2+ The concentration of the standard solution is 10 -3 mol / L~10 -9 mol / L; Pb 2+ The concentration of the standard solution is 200~0.1 ppm; Co 2+ The concentration of the standard solution is 10 -3 mol / L~10 -7 mol / L; (3) Perform Raman spectroscopy on the solution to be tested The solution to be tested containing heavy metal cations is dropped onto the surface of the test paper, and the solution after the reaction is subjected to Raman spectroscopy detection. The concentration of the heavy metal cations can be calculated by the Raman signal standard curve of the corresponding heavy metal cations, thereby realizing the quantitative detection of the heavy metal cations in the solution to be tested; the concentration of the heavy metal cations in the solution to be tested is 0.01 mol / L~10 -9 mol / L; the heavy metal cation in step (3) is Cd 2+ , Pb 2+ 、Co 2+ One or more of the following; Wherein, the anion in step (1) is iodide ion, Cd 2+ The iodine ions loaded on the test paper produce precipitation interference Raman signal; or the anion in step (1) is sulfate ion, Pb 2+ The solution and the sulfate ions loaded on the test paper generate precipitation to interfere with the Raman signal; or the anions in step (1) are phosphate ions and iodide ions, Cd 2+ The solution and the iodine ions loaded on the test paper generate precipitation that interferes with the Raman signal. 2+ The solution and the phosphate ions loaded on the paper-based chip produce precipitation interference Raman signal; or the anions in step (1) are phosphate and sulfate ions, Pb 2+ 、Co 2+ They interfere with the Raman signal respectively.
2. The method according to claim 1, characterized in that The gold source used in preparing the gold nanoparticles in step (1) is tetrachloroauric acid trihydrate, and the mass ratio of tetrachloroauric acid trihydrate to quaternized xylan is 5-40 mg: 0.1-2 g; the reduction reaction time is 30-60 min, and the reduction reaction temperature is 70-90 ° C; the gold nanoparticle coating amount is 1.5-6.5 g / m 2 .
3. The method according to claim 1, characterized in that The specific steps of in situ reduction of silver nanoparticles on the paper surface in step (1) are as follows: placing the paper coated with the gold nanoparticle dispersion into Tollens reagent at 50-80°C for reaction for 30-60 min, and depositing the silver nanoparticles obtained by in situ reduction on the surface of the paper coated with the quaternary ammonium xylan gold nanoparticles, and then vacuum drying the treated test paper at 50°C for 12-24 h.
4. The method according to claim 1, characterized in that The concentration of anions in the anion-containing solution in step (1) is 0.01 mol / L to 1 mol / L; the ion exchange time is 1 to 3 h, and vacuum drying is performed after the ion exchange reaction is completed.
5. The method according to claim 1, characterized in that The ion exchange method used in step (1) is at least one of immersion and elution.
6. The method according to claim 1, characterized in that In step (1), the Raman beacon molecule is added to the test paper after ion exchange, specifically, the Raman beacon molecule solution is dripped onto the surface of the test paper after ion exchange, and then dried at room temperature; the Raman beacon molecule is at least one of 4-thiobenzoic acid, crystal violet, and rhodamine 6G; the concentration of the Raman beacon molecule solution is 10-100 mmol / L.
7. The method according to any one of claims 1 to 6, characterized in that: The Raman spectrum wavelength used in the Raman spectrum detection in steps (2) and (3) is at least one of 532 nm, 633 nm, and 785 nm, and the intensity of the Raman spectrum used is at least one of 5%, 3.2%, 1%, and 0.1%.
Citation Information
Patent Citations
Method for preparing quaternary ammonium salt of chitosan for adsorbing uranium
CN106944014A
Quaternized xylan coating mercury ion detection paper-based chip and preparation method and application thereof
CN118847241A